If f(x)=x^2-3f(x)=x23 and g(x)=5xg(x)=5x, how do you find f(g(-3))?

2 Answers
Jul 28, 2018

222

Explanation:

first, find f(g(x))f(g(x))

f(g(x))=(5x)^2-3f(g(x))=(5x)23

f(g(x))=25x^2-3f(g(x))=25x23

now, put x=-3x=3

f(g(-3))=25*9-3f(g(3))=2593

f(g(-3))=222f(g(3))=222

Jul 28, 2018

f(g(-3))=222f(g(3))=222

Explanation:

"begin by evaluating "g(-3)begin by evaluating g(3)

g(-3)=5xx-3=-15g(3)=5×3=15

"now evaluate "f(g(-3))tof(-15)now evaluate f(g(3))f(15)

f(-15)=(-15)^2-3=225-3=222f(15)=(15)23=2253=222